The nature and structure of the concept of "professional competence" (Pedagogy of Higher and Secondary Education, 2012)
Shiba A. The nature and structure of the concept of "professional competence".The paper deals with the nature of specialist’s professional competence and its structure. The author also presents her definition of the notion “professional competence”.
Keywords: competence; professional competence; the structure of the professional competence